A coupled BEM/FEM formulation for drop interaction in Stokes flows with flexible and slip confining boundaries. (April 2017) - Soares, Delfim; Wrobel, Luiz C.
Abstract: In this work, fluid-fluid-solid coupled models are analysed, considering the interaction of boundary and finite element techniques. In this context, the paper focuses on the study of deforming drops through bulk fluids bounded by flexible walls. Here, the fluid subdomains are assumed to be viscous and incompressible, and they are modelled by the BEM. The solid subdomains are assumed to be elastic, and they are modelled by the FEM. Both discontinuity of tractions on the fluid-fluid common boundaries and discontinuity of velocities on the fluid-solid interfaces are considered. For the discontinuity of velocities, a formulation based on nonlinear slip boundary conditions is adopted, which is treated employing a relaxed iterative approach. A Lagrangian representation is considered and remeshing is applied on the fluid-fluid interfaces, reducing the appearance of numerical problems. Numerical results are presented to illustrate the performance and potentialities of the proposed techniques.